Electrochemical Determination of Norepinephrine at Poly (p-aminobenzenesulfonic Acid) Modified Sensor - Yağcı, Şevket Zişan; Savan, Ebru K.; Erdoğdu, Gamze (Current Pharmaceutical Analysis, 2020)
Objective: In this study, it was aimed to prepare an electrochemical sensor capable of assigning Norepinephrine in the presence of an interference such as ascorbic acid. Methods: A sensitive modified sensor was prepared by electrodeposition of p-aminobenzenesulfonic acid (p-ABSA) to the glassy carbon electrode by cyclic voltammetry. The electrooxidation of Norepinephrine was accomplished by cyclic and differential pulse voltammetry. Results: The current values were enhanced and the peak potentials of Norepinephrine and ascorbic acid were separated at the sensor compared to the bare electrode. There was linearity between the oxidation current and concentration of Norepinephrine ranging from 0.5 to 99.8 μM in phosphate buffer solution at pH 7.0. The limit of detection was 10.0 nM and the sensitivity was 0.455 μA/μM. Conclusion: The determination of Norepinephrine was successfully performed in real samples such as blood serum and urine at the poly (p-ABSA) sensor. To the best of our knowledge, this is the first study to detect Norepinephrine in the presence of ascorbic acid at poly (p-ABSA) modified sensor in the literature.
Keywords: voltammetry